REGENT’S LIABILITY FOR RECEIVING BRIBERY OF PROCUREMENT OF GOODS/SERVICES - Tanjung, Ahmad Feri; Sianturi, Ronald Hasudungan; Christian Naldo, Rony Andre (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article aims to examine the application of criminal liability to the Regent because he received bribes related to the procurement of goods/services. The act of receiving bribery is an action that is contrary to the law, especially the provisions of Article 12 B of Law Number 20 of 2001 Concerning Eradication of Corruption Crimes. The problem is focused on the application of the criminal liability of the Labuhan Batu Regent because he received bribes related to the procurement of goods/services. The theory used in analyzing the problem approach is the Theory of Criminal Liability put forward by Dwidja Priyatno. According to Dwidja Priyatno, criminal liability was born with an objective reproach against actions stated as criminal acts based on applicable criminal law, and subjectively to perpetrators who meet the requirements to be criminalized because of their actions. Data are collected through primary legal materials, secondary legal materials, as well as tertiary legal materials, and are analyzed qualitatively. This study concluded that the criminal liability applied to the Labuhan Batu Regent because receiving bribes related to the procurement of goods and services is in the form of imprisonment, criminal fines, additional crimes paying replacement money, and additional crimes in the form of revocation of the right to be elected